2019
DOI: 10.1002/admt.201900599
|View full text |Cite
|
Sign up to set email alerts
|

Smart Thermal Management Textiles with Anisotropic and Thermoresponsive Electrical Conductivity

Abstract: Outdoor heat stress can cause health hazards for workers and reduce labor productivity, thus leading to an annual burden of US $6.2 billion for the Australian workforce. Because the outdoor temperature fluctuates within a day, self‐regulating textiles are urgently needed to keep the temperature of the human body stable. Smart textiles are able to sense their surrounding environment and can respond by adapting their behaviors accordingly. However, there are a number of challenges in utilizing functional materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…15 The most representative material in TC materials is vanadium oxide (VO 2 ) or VO 2 -based composite materials, which allows less heat energy at high temperatures than at low temperatures, and vice versa. [16][17][18][19][20][21][22][23] The ultratransparent coating formed of template-free tunable VO 2 hierarchical and honeycomb-like structures shows excellent visible light transparency up to 95.4% at 700 nm with a solar modulation ability of 5.5%. 20 The obtained ultra-transparent honeycomb-like V 2 O 5 /VO 2 film has shown enhanced anti-reflective and transmittance performance, which has also been demonstrated theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…15 The most representative material in TC materials is vanadium oxide (VO 2 ) or VO 2 -based composite materials, which allows less heat energy at high temperatures than at low temperatures, and vice versa. [16][17][18][19][20][21][22][23] The ultratransparent coating formed of template-free tunable VO 2 hierarchical and honeycomb-like structures shows excellent visible light transparency up to 95.4% at 700 nm with a solar modulation ability of 5.5%. 20 The obtained ultra-transparent honeycomb-like V 2 O 5 /VO 2 film has shown enhanced anti-reflective and transmittance performance, which has also been demonstrated theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Given the considerations reported above, the characterization of the thermal properties of PES textiles is of crucial importance. In this respect, it is worth mentioning that both mechanical, electrical [ 9 ] and thermal [ 10 ] properties of fabrics have been shown to be extremely anisotropic and, consequently, woven textiles are also expected to exhibit anisotropic thermal transport properties which are significantly affected by fiber structure. In particular, the heat produced by the current flowing into the electrically conductive yarns has been shown to be mainly spread in the plane of the fibers rather than in the perpendicular direction [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the heat produced by the current flowing into the electrically conductive yarns has been shown to be mainly spread in the plane of the fibers rather than in the perpendicular direction [ 11 , 12 ]. In this regard, it has been recently reported that the presence of anisotropy in the fiber-woven structure [ 9 , 13 , 14 ], such as those due to different density of warp and weft yarns [ 15 ] or yarn count differences in warp and weft directions [ 16 ], may lead to a significant anisotropic behavior of the thermal transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Cephalopods are the king of adaptive camouflage in visible and IR range (Mathger et al, 2009;Mathger and Hanlon, 2007;Yang et al, 2021). Their skin surfaces contain numerous ll OPEN ACCESS chromatophores and structural reflectors, which can tune the interaction between the light and the skins through the muscle contraction and expansion (Phan et al, 2016). Inspired by cephalopods, herein we demonstrate a facile and scalable method for adaptive IR reflection based on a Janus rubber film, which is composed of an AMS/rubber composite top and a rubber-only bottom.…”
Section: Introductionmentioning
confidence: 99%
“…A continuous-range tuning of infrared (IR) features upon matters can enable innovative technologies and applications, such as building insulations ( Granqvist et al., 2017 ; Hu et al., 2018 ), energy-conserving windows ( Ke et al., 2018 ; Lee et al., 2019 ; Liu et al., 2016 ), protective clothing ( Cai et al., 2017 ; Jiang et al., 2016 ; Peng et al., 2020 ), and adaptive IR camouflages for military and commercial purposes ( Yu et al., 2014 ; Chandrasekhar et al., 2003 ; Zhu et al., 2020 ; Gu et al., 2020 ). Two main mechanisms are now established, including the modulation of IR emittance and the control of IR reflection ( Li et al., 2020a ).…”
Section: Introductionmentioning
confidence: 99%